2016
DOI: 10.1016/j.physbeh.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet exposure during the juvenile period increases social behaviors and forebrain neural activation in adult Engrailed 2 null mice

Abstract: Prolonged consumption of ketogenic diets (KD) has reported neuroprotective benefits. Several studies suggest KD interventions could be useful in the management of neurological and developmental disorders. Alterations in the Engrailed (En) genes, specifically Engrailed 2 (En2), have neurodevelopmental consequences and produce autism-related behaviors. The following studies used En2 knockout (KO; En2(-/-)), and wild-type (WT; En2(+/+)), male mice fed either KD (80% fat, 0.1% carbohydrates) or control diet (CD; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 67 publications
1
37
0
Order By: Relevance
“…We also tested the social behaviors of KD‐fed mice with three‐chamber apparatus and found no change in the social exploration preference, suggesting the social behavior is little affected by long‐term feeding of KD. These results are interesting in light that numerous studies have reported beneficial effect of KD in social behaviors in autism patients, animal models of autism and wildtype young adult rats (Ruskin et al, ; Ahn et al, ; Verpeut et al, ; Castro et al, ; Kasprowska‐Liskiewicz et al, ). The real reason for the discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We also tested the social behaviors of KD‐fed mice with three‐chamber apparatus and found no change in the social exploration preference, suggesting the social behavior is little affected by long‐term feeding of KD. These results are interesting in light that numerous studies have reported beneficial effect of KD in social behaviors in autism patients, animal models of autism and wildtype young adult rats (Ruskin et al, ; Ahn et al, ; Verpeut et al, ; Castro et al, ; Kasprowska‐Liskiewicz et al, ). The real reason for the discrepancy is not clear.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, KD is shown to increase sociability in young male rats (Kasprowska‐Liskiewicz et al, ). However, it exhibited minimal effect in other studies (Ruskin et al, ; Verpeut, DiCicco‐Bloom, & Bello, ; Castro, Baronio, Perry, Riesgo, & Gottfried, ). The reasons for these inconsistencies are not very clear, possibly due to variation in animal husbandry and/or experimental designs.…”
Section: Introductionmentioning
confidence: 80%
“…In both male and female MIA offspring a KD increased time spent in direct social contact with another mouse during the three-chamber test; in females this increase resulted in higher social contact time than control animals [ 34 ]. Studies using rodent ASD models with diverse etiologies [strain (mouse: BTBR and EL), genetic (mouse: Engrailed 2 knockout), gestational exposure (rat: valproic acid)] have also shown elevated sociability after KD feeding in three-chamber tests [ 24 26 , 28 ]. In addition, a KD normalizes play behavior in juvenile rats in the gestational valproic acid model [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This includes case studies in children describing improvements in core symptoms (as well as seizures) [ 19 , 20 ] and small pilot studies reporting varied responses including improvements during KD use [ 21 23 ]. More recently, studies have shown that KD treatment improves sociability and reduces self-directed repetitive behavior in animal models of ASD such as the BTBR T+ tf/J mouse strain [ 24 ], the EL mouse strain [ 25 ] and mice with genetic inactivation of the Engrailed 2 gene [ 26 ]. Specifically for environmentally-induced ASD, KD feeding improves sociability and repetitive behavior in the gestational valproic acid model in rats [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming apparent that beneficial effects of ketogenic therapy extend beyond epilepsy, neurodegenerative disorders, and brain/spinal cord injury. The KD is broadly effective in improving core behavioral symptoms in animal models of autism spectrum disorder (Ruskin et al, 2013b , 2017a , b ; Ahn et al, 2014 ; Verpeut et al, 2016 ; Castro et al, 2017 ; Dai et al, 2017 ), and in autistic patients (Evangeliou et al, 2003 ; Masino et al, 2011b ; Spilioti et al, 2013 ). The KD is receiving growing interest in oncology as tumors are highly glucose-dependent (the Warburg effect; Seyfried and Mukherjee, 2005 ; Zuccoli et al, 2010 ; Schmidt et al, 2011 ; Klement et al, 2016 ; Lussier et al, 2016 ; Khodadadi et al, 2017 ).…”
Section: Introduction: Ketogenic Diet and Disorders Of The Nervous Symentioning
confidence: 99%